VIABILITY OF THE IMPLEMENTATION OF ELECTRONIC INVOICE IN MYPIMES OF CIUDAD DEL ESTE - Gabriel Román Molinas, Nelson; Giselle Gonzalez Espinola, Lariza; Beatriz Casco Rojas, Gabriela; Daniel Morel Mongelos, Francisco; Vanessa Ruiz Diaz de Salvioni, Viviana (Revista Gênero e Interdisciplinaridade, 2023)
This research work focuses on the Feasibility of the Implementation of Electronic Billing in MYPIMES of Ciudad del Este. The general objective is to analyze the level of viability of the implementation of electronic invoicing in MYPIMES, conducting surveys to know the opinion of each of the managers or owners, if they are aware of electronic invoicing and will have the necessary resources to implement the electronic billing. To achieve this objective, a quantitative approach was used, with a population of 20 small and medium-sized companies in the field of retail sales in pantries, corresponding to km 8 Barrio San Pedro, km 7 Barrio Ciudad Nueva and km 6/5 Barrio San Isidro, from Ciudad del Este. A survey of closed questions was applied to collect the necessary data.The results of this research will provide valuable information on the possibility of introducing electronic invoicing in MYPIMES in the area, which could have a significant impact on the financial and administrative management of these companies.